Melody & Rhythm permutatios: more than 300 exercises for mallets and other instruments - Richards, Emil. 1932-2019 (Hal Leonard Corporation, 2009)
The exercises in Melody & Rhythm Permutations were developed to improve sight reading and improvisational skills in the advanced player.